HCV entry and neutralizing antibodies: lessons from viral variants. (June 2009) - Zeisel, Mirjam B; Baumert, Thomas F
Evaluation of: Grove J, Nielsen S, Zhong J et al. : Identification of a residue in hepatitis C virus E2 glycoprotein that determines scavenger receptor BI and CD81 receptor dependency and sensitivity to neutralizing antibodies. J. Virol. 82 (24), 12020––12029 (2008). Recent data suggest that a strong, early, broad neutralizing antibody response may contribute to the control of HCV in the acute phase of infection. However, the majority of individuals fail to clear HCV during the first months following infection and develop chronic infection despite the presence of anti-HCV antibodies. A prerequisite of the understanding behind the mechanisms of viral escape from antibody-mediated neutralization is the identification of various host-entry factors mediating the first steps of viral infection –– binding and entry of HCV is believed to be a multistep process involving HCV envelope glycoproteins E1 and E2 as well as several host-cell surface molecules such as CD81, scavenger receptor class B type I, members of the claudin family and occludin. In this article, Grove et al. describe a single mutation in the HCV envelope glycoprotein E2 that alters glycoprotein structure thereby modulating viral interaction with scavenger receptor class B type I and CD81, and increasing sensitivity to neutralizing antibodies. The results of this study highlight the importance of the characterization of the interplay between HCV particles and host-cell factors for the understanding of virus neutralization by host-immune responses and pathogenesis of HCV infection.